Analisis Ketersediaan Dan Kebutuhan Ruang Terbuka Hijau Pada Kawasan Pusat Pelayanan Kota (Studi Kasus Kecamatan Palu Timur, Kota Palu) - ACHSAN, ANDI CHAIRUL (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Analysis of the Availability and Requirements of Green Open Space on Service Centre Area of The City (Case Study on Palu Timur District, Palu City) The development on urban growth at this time indicates unbalance movement activities, where many of it should have be able to maintain and ensure its sustainability of resources and preservation of environmental quality. One effort to minimize the negative impact of the environmental hazards against physical development in urban area is through green open space planning. The purpose of this study was to identify and analyze the needs and availability of green open space in the service center area of Palu city based on area, population and need for oxygen. The results showed that the availabilty of existing green open space in the service centre area of Palu city was 39,49 hectare and the result of green open space requirement in Palu service centre area based on area, population and need for oxygen were 180 hectare, 78,81 hectare and 43,89 hectare respectively. Keywords : green open space, availability, needs